Choosing nursing as a career: a narrative analysis of millennial nurses' career choice of virtue. Issue 4 (3rd April 2013) - Price, Sheri Lynn; McGillis Hall, Linda; Angus, Jan E; Peter, Elizabeth
<x xml:space="preserve">Abstract</x> The growth and sustainability of the nursing profession depends on the ability to recruit and retain the upcoming generation of professionals. Understanding the career choice experiences and professional expectations of Millennial nurses (born 1980 or after) is a critical component of recruitment and retention strategies. This study utilized Polkinghorne's interpretive, narrative approach to understand how Millennial nurses explain, account for and make sense of their choice of nursing as a career. The positioning of nursing as a virtuous choice was both temporally and contextually influenced. The decision to enter the profession was initially emplotted around a traditional understanding of nursing as a virtuous profession: altruistic, noble, caring and compassionate. The centricity of virtues depicts one‐dimensional understanding of the nursing profession that alone could prove dissatisfying to a generation of professionals who have many career choices available to them. The narratives reveal how participants' perceptions and expectations remain influenced by a stereotypical understanding of nursing, an image that remains prevalent in society and which holds implications for the future recruitment, socialization and retention strategies for upcoming and future generations of nurses.